Synthesis and application of dynamic self-supported enantioselective catalysts - Bellemin-Laponnaz, Stéphane; Achard, Thierry; Bissessar, Damien; Geiger, Yannick; Maisse-François, Aline (Coordination chemistry reviews, 2017)
[Display omitted] •An overview of dynamic self-supported chiral catalysts is outlined.•General considerations for the design of dynamic self-supported chiral catalysts are discussed.•Strengths and limitations of the systems are analyzed. Since chiral coordination complexes have a broad scope for asymmetric synthesis, their immobilization has been the subject of intensive research. Indeed, the immobilization of chiral catalysts is an appealing approach to solve problems such as product contamination or catalyst reuse. Numerous approaches have been developed and despite promising results each immobilization technique displays several strengths and limitations that make them highly specific. During the last years, dynamic self-supported catalysis has emerged as an alternative and new strategy to circumvent some limitations of classical immobilized catalysts. In such system, a metal-organic self-assembly is in equilibrium with discrete monomeric active species, a case that offers exciting opportunities for catalysis. Recent work in this area shows that these systems can compete with their homogeneous counterparts. This review highlights the recent developments in the growing field of dynamic self-supported asymmetric catalysis.